Tracked Changes. Paints and varnishes. Evaluation of properties of coating systems related to the spray application process. Colour stability, process hiding power, re-dissolving, overspray absorption, wetting, surface texture and mottling Part 2, (25th November 2021) - British Standards Institution,
No abstract available